Two-Minute Step Test as a Complement to Six-Minute Walk Test in Subjects With Treated Coronary Artery Disease - Oliveros, María José; Seron, Pamela; Román, Claudia; Gálvez, Manuel; Navarro, Rocío; Latin, Gonzalo; Marileo, Tania; Molina, Juan Pablo; Sepúlveda, Pablo; Marzuca-Nassr, Gabriel Nasri; Muñoz, Sergio (Frontiers in Cardiovascular Medicine, 2022)
The Two-minutes Step Test (2MST) has been presented as an alternative to the Six-minute walk test (6MWT) based on the association between the two tests in older adults, however some authors propose that it should not be a substitute but rather a complement in the fitness evaluation. Specifically, in coronary artery disease, despite the potential and clinical utility of 2MST, the relationship of both tests in this population is unknown. This study aims to determine the relationship between 6MWT and 2MST, secondarily to explore the relationship of bio-demographic factors for both tests in subjects with treated cardiovascular disease. For this, 6MWT and 2MST were applied to patients with coronary artery disease treated in 6 hospitals in Chile, between May 2019 and February 2020. Additionally, lower limb strength assessed by chair stand test, grip strength assessed by dynamometer, and physical measurements were applied. One hundred sixty-three participants performed both tests (average age=58.7±9.8 years; 73.6% male; 64.4% revascularized by angioplasty; 28.2% revascularized by surgery and 7.4% was treated by drugs or thrombolysis). Heart rate was higher at the end of 6MWT while perception of effort was greater at the end of the 2MST. There was a weak positive correlation between 6MWT and 2MST in subjects with treated coronary disease (r=0.28, p=0.0003). While age (r = -0.27), weight (r= 0.25), height (r= 0.49), and strength of both lower limbs (r=0.41) and grip strength (r=0.53) correlate weakly or moderately to covered distance in 6MWT, the number of steps by 2MST correlates only weakly to height (r= 0.23), lower limb strength (r= 0.34) and grip strength (r= 0.34). Age, weight, height, lower limb strength and grip strength would explain better the meters walked in the 6MWT than the steps achieved in the 2MST. With these findings we can conclude that in patients with treated coronary disease, it does not seem advisable to replace 6MWT with 2MST when it is possible to do so. Additionally, 2MST may provide additional information in the fitness evaluation. However, the usefulness of 2MST in this population needs to be further studied.